Correspondência verbal: efeitos da instrução do experimentador sobre os comportamentos verbal e não verbal e sobre o seguimento de instrução de crianças - Melo, Luiz Felipe Silva (2014)
Studies developed by behavior analysts have shown that different contingencies of reinforcement produce different relationships between nonverbal and verbal behaviors. This study is part of this research area and aimed to verify the effects of the experimenter's instruction on playing, on reporting and on following instructions by children when different contingencies of reinforcement are in effect. Five-year-old children were the participants. In each session, participants went through a period of play, followed by a period in which they reported on toys they had played with. In the reporting period, the children went through five phases of baseline throughout the study and seven experimental phases:: a) Instruction for playing with a particular toy a low preference one , with no consequence following the report; b) Instruction for playing with three toys the same as before, but with three toys; c) Reinforcement of verbalization in group of following the instruction of a toy children received instruction to play with a particular low preference toy, and reinforcement was contingent only on the report of having played with that toy; d) Reinforcement of verbalization in group of following the instruction with three toys the same as phase c, but with three toys; e) Reinforcement for following instruction and correspondence in group of a toy similar to phase c, but the child's behavior was reinforced only if there was correspondance with playing; f) Reinforcement for following instruction and correspondence in group of three toys similar to phase e, but with three toys; and g) Non-contingent reinforcement. Most participants maintained correspondence between their verbal and nonverbal behaviors in throughout the study. When reporting having played with the three target toys was enough for the release of reinforcement, one of the participants went on to report having played with all the toys. When the correspondence as to the following of instruction has been reinforced, all participants, at different times, started to play with the target toys, and the participant who had gone on to report having played with all the the toys, went back to corresponding reports